A Rational Design of Metal–Organic Framework Nanozyme with High-Performance Copper Active Centers for Alleviating Chemical Corneal Burns - Tang, Yonghua; Han, Yi; Zhao, Jiachen; Lv, Yufei; Fan, Chaoyu; Zheng, Lan; Zhang, Zhisen; Liu, Zuguo; Li, Cheng; Lin, Youhui (Nano-Micro Letters, 2023)
Metal–organic frameworks (MOFs) have attracted significant research interest in biomimetic catalysis. However, the modulation of the activity of MOFs by precisely tuning the coordination of metal nodes is still a significant challenge. Inspired by metalloenzymes with well-defined coordination structures, a series of MOFs containing halogen-coordinated copper nodes (Cu-X MOFs, X = Cl, Br, I) are employed to elucidate their structure–activity relationship. Intriguingly, experimental and theoretical results strongly support that precisely tuning the coordination of halogen atoms directly regulates the enzyme-like activities of Cu-X MOFs by influencing the spatial configuration and electronic structure of the Cu active center. The optimal Cu–Cl MOF exhibits excellent superoxide dismutase-like activity with a specific activity one order of magnitude higher than the reported Cu-based nanozymes. More importantly, by performing enzyme-mimicking catalysis, the Cu–Cl MOF nanozyme can significantly scavenge reactive oxygen species and alleviate oxidative stress, thus effectively relieving ocular chemical burns. Mechanistically, the antioxidant and antiapoptotic properties of Cu–Cl MOF are achieved by regulating the NRF2 and JNK or P38 MAPK pathways. Our work provides a novel way to refine MOF nanozymes by directly engineering the coordination microenvironment and, more significantly, demonstrating their potential therapeutic effect in ophthalmic disease. Highlights: 1 Inspired by metalloenzymes with well-defined coordination structures, a series of Cu-X metal–organic frameworks (MOFs) nanozymes with tunable copper active centers were successfully constructed. 2 Experimental and theoretical results strongly supported that precisely tuning the coordination of halogen atoms could directly regulate the enzyme-like activities of Cu-X MOFs by influencing their spatial configuration and electronic structure. 3 The optimal Cu–Cl MOF with excellent enzyme-mimicking activities could effectively relieve ocular chemical burns by possible antioxidant and antiapoptotic mechanisms.